Utilization of Black Tea Dregs as an Adsorbent of Metal Fe in Water using UV-Vis Spectrophotometry - sauli safitri; Sitti Aminah; Yuli Nurmayanti; Sitti Rahmawati; Tri Santoso (Universitas Tadulako, 2025)
Tea dregs are household organic waste materials that can be utilized as low-cost adsorbents for heavy metal removal. Previous studies mainly employed green tea dregs and focused on Cu(II) adsorption, while studies on Fe(III) adsorption using black tea dregs and their direct application to Fe-contaminated water remain limited. This study evaluates the adsorption performance of black tea dregs toward Fe(III) ions and their application in water samples. Batch adsorption experiments were conducted using FeCl₃ solutions at pH 4.8 to determine the optimum contact time (15–90 minutes) and initial concentration (100–300 ppm). Fe(III) concentrations were analyzed using UV–Vis spectrophotometry. The results demonstrated an optimal contact time of 60 min and an optimal concentration, achieving 99.26% adsorption efficiency. Adsorption followed the Langmuir isotherm model with a maximum capacity of 37.04 mg/g (R² = 0.998). Application to well water samples resulted in 83.74% Fe removal, confirming the potential of black tea dregs as adsorbents.